Role of 5-HT2C receptors of the dorsal hippocampus in the modulation of anxiety- and panic-related defensive responses in rats - Sant'Ana, Ana Beatriz; Vilela-Costa, Heloisa Helena; Vicente, Maria Adrielle; Hernandes, Paloma Molina; de Andrade, Telma Gonçalves Carneiro Spera [UNESP]; Zangrossi, Hélio (Elsevier, 2019)
The role of 5-HT2C receptors (5-HT2CRs) in the regulation of anxiety has been widely acknowledged. However, conflicting results have been reported on whether stimulation of these receptors increases or decreases anxiety. We here investigated the role of 5-HT2CRs of the dorsal hippocampus (DH) in the mediation of anxiety- or panic-associated defensive behaviors and in the anxiolytic effect of the tricyclic antidepressant imipramine. In the Vogel conflict test, administration of the mixed 5-HT2CR agonist mCPP into the DH of male Wistar rats was anxiogenic, whereas infusions of the more selective agonists MK-212 and RO-600175 were anxiolytic. The 5-HT2CR antagonist SB-242084, on the other hand, was anxiogenic. A sub-effective dose of this antagonist blocked the anxiolytic effect of RO-600175, but not the increase in anxiety observed with mCPP, indicating that the latter effect was not due to 5-HT2CR activation. In full agreement with these findings, MK-212 and RO-600175 in the DH also inhibited inhibitory avoidance acquisition in the elevated T-maze, whereas SB-242084 caused the opposite effect. None of these drugs interfered with escape expression in this test, which has been associated with panic. Chronic administration of imipramine (15 mg/kg, ip, 21 days) caused an anxiolytic effect in the elevated T-maze and light-dark transition tests, which was not blocked by previous infusion of SB-242084 into the DH. Therefore, facilitation of 5-HT2CR-mediated neurotransmission in the DH decreases the expression of anxiety-, but not panic-related defensive behaviors. This mechanism, however, is not involved in the anxiolytic effect caused by imipramine.
Keywords: 5-HT2C receptor; Anxiety; Dorsal hippocampus; Elevated T-maze; Imipramine; Serotonin